Oral conditions and the impact on quality of life of morbidly obese and bariatric patients - Rosana Leal do PRADO; Nataly Dara Moraes SANTOS; Karina Evangelista da SILVA; Maria Carolina RODRIGUES; Jefferson Yoshiharu de Toledo TAGUTI; Juliane Avansini MARSICANO (RGO: Revista Gaúcha de Odontologia, 2020)
ABSTRACT Objective The aim was to evaluate the prevalence of dental caries, periodontal disease and edentulism in morbidly obese and bariatric patients, and to verify the oral health impact on quality of life. Methods We evaluated 33 morbidly obese patients (G1) and 50 patients submitted to bariatric surgery (G2). The DMFT, CPI, prosthetic status and prosthetic need for edentulism were used to analyze oral conditions. The impact of oral health on quality of life was assessed using the OIDP questionnaire. Results CPOD were G1: 9.0±7.0 and G2: 13.3±8.0 (p= 0.020). The dental calculus was the worst periodontal condition G1: 72.7% and G2: 80.0% (p= 0.752). The majority of G1 and G2 patients did not use (p = 0.878) and did not need (p= 0.132) dental prosthesis. The mean of OIDP was G1: 11.2±23.8 and G2: 14.16±23.8 (p= 0.089). Conclusion It concluded that bariatric patients have a higher prevalence of dental caries and the need for dental prostheses is related to the impact of oral health on the quality of life of obese patients.